An analytical solution to the heat transfer problem in thick-walled hunt flow - Bluck, Michael J; Wolfendale, Michael J (The International journal of heat and fluid flow, 2017)
•Convective heat transfer in Hunt type flow of a liquid metal in a rectangular duct.•Analytical solution to the H1 constant peripheral temperature in a rectangular duct.•New H1 result demonstrating the enhancement of heat transfer due to flow distortion by the applied magnetic field.•Analytical solution to the H2 constant peripheral heat flux in a rectangular duct.•New H2 result demonstrating the reduction of heat transfer due to flow distortion by the applied magnetic field.•Results are important for validation of CFD in magnetohydrodynamics and for implementation of systems code approaches. The flow of a liquid metal in a rectangular duct, subject to a strong transverse magnetic field is of interest in a number of applications. An important application of such flows is in the context of coolants in fusion reactors, where heat is transferred to a lead-lithium eutectic. It is vital, therefore, that the heat transfer mechanisms are understood. Forced convection heat transfer is strongly dependent on the flow profile. In the hydrodynamic case, Nusselt numbers and the like, have long been well characterised in duct geometries. In the case of liquid metals in strong magnetic fields (magnetohydrodynamics), the flow profiles are very different and one can expect a concomitant effect on convective heat transfer. For fully developed laminar flows, the magnetohydrodynamic problem can be characterised in terms of two coupled partial differential equations. The problem of heat transfer for perfectly electrically insulating boundaries (Shercliff case) has been studied previously (Bluck et al., 2015). In this paper, we demonstrate corresponding analytical solutions for the case of conducting hartmann walls of arbitrary thickness. The flow is very different from the Shercliff case, exhibiting jets near the side walls and core flow suppression which have profound effects on heat transfer.